The Effect of Insecticide, Monocrotophos in Dividing Cells of Allium cepal and Study of its Mitotic Index (Journal of Tikapur Multiple Campus, 2018)
The effect of moncrotophos, insecticidehas been studied in root tip of Allium cepa. The study shows that monocrotophos induced mitodespersive effect and cytological abnormalities. The abnormalities like plasmolysed cells, c-metaphase, stickymetaphase, precociousarms, laggard, bridge, fragmentation of chromosomes, delayed cytokinesis and bi and tri nucleated were observed.The mitotic index, prophase index, metaphase index and anaphase and telo phase index were obtained.